Predictors of knowledge of blood pressure - a descriptive study - Šedová, Lenka; Bártlová, Sylva; Hudáčková, Andrea; Havierniková, Lucie; Dolák, František (Cardiology letters, 2022)
Goal: The goal of the study was to identify the number of individuals treated for hypertension, to verify the degree of their knowledge of their topical values of systolic and diastolic pressure, and to find out the dependence of regular BP measuring in the home setting on selected socio-demographic factors. Methodology: The quantitative study was performed using the method of standardized face-to-face interviews. The sample consisted of 1,004 respondents. The data were collected using a non-standardized questionnaire focused on stroke prevention and relating selected factors. Results: The investigation identified more than 58% of patients treated for hypertension. More than 50% (n=559) of respondents knew their topical BP values. In 1/3 of them the BP values corresponded with hypertension, 29.2% (175) mentioned the systolic BP ≥ 140 mmHg, and 28.9% (173) mentioned BP ≥ 90 mmHg 260 respondents (25.9%) regularly measure their BP in the home setting. The topical knowledge of BP and regular BP measuring depended on the age, marital status, occupation and education (p<0.001). Individuals regularly visiting their GPs knew the BP values better and performed regular BP measuring in the home setting more frequently. Conclusion: More than 50% of respondents knew their BP values at the time of the study. According to the announced BP values, 1/3 of the sample reached the hypertension values of (≥ 140/90 mmHg). The knowledge of BP and regular BP measuring depended on the age, marital status, occupation and education, and regular visits to general practitioners.